PENDEKATAN PERILAKU KOGNITIF DALAM PELATIHAN KETERAMPILAN MENGELOLA KECEMASAN BERBICARA DI DEPAN UMUM - Fatma, Anne; Ernawati, Sri (Universitas Sahid Surakarta, 2012)
ThisÂ researchÂ aimedÂ toÂ understandÂ theÂ effectivenessÂ ofÂ TrainingÂ onÂ theÂ SkillÂ of ManagingÂ PublicÂ SpeakingÂ AnxietyÂ UsingÂ Cognitive-BehavioralÂ Approach,Â onÂ theÂ wayÂ it can reduce the level of Public Speaking Anxiety. The experiment design used in this research is Non-randomized Pre-test and Post-testÂ ControlÂ GroupÂ Design,Â withÂ theÂ subjectsÂ were 20Â undergraduateÂ studentsÂ ofÂ Sahid University Surakarta experiencing public speaking anxiety. TheÂ resultÂ ofÂ statisticalÂ analysisÂ usingÂ theÂ Mann-WhitneyâsÂ testÂ areÂ :Â thereÂ was significantly different level of public speaking anxiety between the experimental group and control group at pre-test and post-test, with z =Â -2,374 (p<0,01). The phi square is 0,5388. It means that the training gave 53,88% on reducing the level of public speaking anxiety. The model of Training on the Skill of Managing Public Speaking Anxiety Using Cognitive-BehavioralÂ ApproachÂ wasÂ effectiveÂ toÂ reduceÂ theÂ levelÂ ofÂ publicÂ speakingÂ anxiety.Â So,Â it was matched with the hypothesis of this research.